The review of prospective studies on mental health and the quality of life of physicians and medical students - Szymon Szemik; Maksymilian Gajda; Małgorzata Kowalska (Nofer Institute of Occupational Medicine, 2020)
Psychosocial determinants play a significant role in shaping mental health and the quality of life of workers, including physicians. The results of the presented review indicate that mental health problems of physicians are particularly manifested by chronic fatigue syndrome and burnout syndrome, and are related to chronic stress exposure at the workplace. Moreover, published data suggest that the most important mental health problems of medical students and young doctors include alcohol addiction and risky alcohol consumption, depression, and potential suicidal ideation. The studies on mental health and the quality of life of physicians, including their determinants, as presented in this paper, were mostly conducted on the basis of prospective observations that enable the tracking of changes over time. Med Pr. 2020;71(4):483-91